2021
DOI: 10.1200/po.20.00246
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Clinical and Polygenic Factors to Predict Breast Cancer Risk in Women Undergoing Genetic Testing

Abstract: PURPOSE Screening and prevention decisions for women at increased risk of developing breast cancer depend on genetic and clinical factors to estimate risk and select appropriate interventions. Integration of polygenic risk into clinical breast cancer risk estimators can improve discrimination. However, correlated genetic effects must be incorporated carefully to avoid overestimation of risk. MATERIALS AND METHODS A novel Fixed-Stratified method was developed that accounts for confounding when adding a new fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…However, it has been previously shown that this potential bias can be avoided by accounting for family history in the logistic regression model. 1 , 16 , 18 , 26 Second, this study used only women of European ancestry. Further studies are required to examine polygenic breast cancer risk for women of non-European ancestry, including PV carriers and noncarriers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has been previously shown that this potential bias can be avoided by accounting for family history in the logistic regression model. 1 , 16 , 18 , 26 Second, this study used only women of European ancestry. Further studies are required to examine polygenic breast cancer risk for women of non-European ancestry, including PV carriers and noncarriers.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 28 Although future work may expand the SNP profiles for commercially available PRSs, this and other recent work show that these risk models provide important clinical information to inform individual patient cancer risks. 15 , 16 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical models such as the Tyrer-Cuzick [ 11 ] and the ‘Breast and Ovarian Analysis of Disease Incidence and Carrier Estimation Algorithm (BOADICEA)’ [ 12 ] integrate the PRS and NGRF and can now provide a more precise and accurate BC risk prediction than family history or monogenic testing alone. Based on this estimation, more personalized recommendations, such as increased breast surveillance at a younger age than standard recommendation, can be delivered for BC risk management.…”
Section: Introductionmentioning
confidence: 99%